Pengelolaan Dana Zakat untuk Pemberdayaan Pendidikan Anak Yatim Dhuafa : Indonesia - Kharina Arifia; Dita Khoirunjannah (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2024)
Ziswaf (Zakat, Infaq, Sadaqah and Waqf) is the practice of giving gifts or endowments in Islam. Ziswaf plays a very important role in teaching Islam in a social, economic and spiritual context. The Ziswaf program itself aims to facilitate the practice of Ziswaf in society. This program can take the form of a zakat, infaq, sadaqah and waqf collection program organized by social or religious institutions. The aim of this research is to examine how zakat funds are managed to empower the education of orphans and poor people in Yatim Mandiri Pasuruan. The research carried out in this study used qualitative methods with the aim of interpreting and describing the data in question. The qualitative method we use in this research is a literature study. Literature study is a research method in which information is sought through books, magazines and other literature. The Ziswaf program aims to facilitate the practice of ziswaf to make it easier and more effective and ensure its usefulness. managed well and used for purposes that are truly beneficial to society